INTERNALIZATION AND DEGRADATION OF THE GLUTAMATE TRANSPORTER GLT-1 IN RESPONSE TO PHORBOL ESTER - Susarla, Bala T.S. (2007)
Activation of protein kinase C (PKC) decreases the activity and cell surface expression of the predominant forebrain glutamate transporter, GLT-1. In the present study, C6 glioma were used as a model system to define the mechanisms that contribute to this decrease in cell surface expression and to determine the fate of internalized transporter. As was previously observed, phorbol 12-myristate 13-acetate (PMA) caused a decrease in biotinylated GLT-1. This effect was blocked by sucrose or by co-expression with a dominant-negative variant of dynamin 1, and it was attenuated by co-expression with a dominant-negative variant of the clathrin heavy chain. Depletion of cholesterol with methyl-β-cyclodextrin, co-expression with a dominant-negative caveolin-1 mutant (Cav1/S80E), co-expression with dominant-negative variants of Eps15 (epidermal-growth-factor receptor pathway substrate clone 15), or co-expression with dominant-negative Arf6 (T27N) had no effect on the PMA-induced loss of biotinylated GLT-1. Long-term treatment with PMA caused a time-dependent loss of biotinylated GLT-1 and decreased the levels of GLT-1 protein. Inhibitors of lysosomal degradation (chloroquine or ammonium chloride) or co-expression with a dominant-negative variant of a small GTPase implicated in trafficking to lysosomes (Rab7) prevented the PMA-induced decrease in protein and caused an intracellular accumulation of GLT-1. These results suggest that the PKC-induced redistribution of GLT-1 is dependent upon clathrin-mediated endocytosis. These studies identify a novel mechanism by which the levels of GLT-1 could be rapidly down-regulated via lysosomal degradation. The possibility that this mechanism may contribute to the loss of GLT-1 observed after acute insults to the CNS is discussed.